Dampak Penggunaan Bahasa Daerah Terhadap Pembelajaran Bahasa Indonesia di SMKN 1 Loksado - Misna (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the impact of the use of regional languages ​​in everyday life on learning Indonesian at SMKN 1 Loksado. In a multilingual environment like Loksado, where regional languages ​​such as Meratus and Banjar are used dominantly, there is a shift in students' attitudes and understanding of Indonesian. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that intensive use of regional languages ​​affects students' ability in speaking Indonesian, both in terms of vocabulary, sentence structure, and pronunciation. Although regional languages ​​enrich local culture, a balanced pedagogical approach is needed so that students are still able to master Indonesian properly and correctly.